Unexpected XPS Binding Energy Observations Further Highlighted by DFT Calculations of Ruthenocene-Containing [IrIII(ppy)2(RCOCHCORc)] Complexes: Cytotoxicity and Crystal Structure of [Ir(ppy)2(FcCOCHCORc)] - Blenerhassitt E. Buitendach; Elizabeth Erasmus; Eleanor Fourie; Frederick P. Malan; Jeanet Conradie; J. W. (Hans) Niemantsverdriet; Jannie C. Swarts (Molecules)
The series of iridium(III) complexes, [Ir(ppy)2(RCOCHCOR′)], with R = CH3 and R′ = CH3 (1), Rc (2), and Fc (3), as well as R = Rc and R′ = Rc (4) or Fc (5), and R = R′ = Fc (6), ppy = 2-phenylpyridinyl, Fc = FeII(η5–C5H4)(η5–C5H5), and Rc = RuII(η5–C5H4)(η5–C5H5), has been investigated by single-crystal X-ray crystallography and X-ray photoelectron spectroscopy (XPS) supplemented by DFT calculations. Here, in the range of 3.74 ≤ ΣχR ≤ 4.68, for Ir 4f, Ru 3d and 3p and N 1s orbitals, binding energies unexpectedly decreased with increasing ΣχR (ΣχR = the sum of Gordy group electronegativities of the R groups on β-diketonato ligands = a measure of electron density on atoms), while in Fe 2p orbitals, XPS binding energy, as expected, increased with increasing ΣχR. Which trend direction prevails is a function of main quantum level, n = 1, 2, 3…, sub-quantum level (s, p, d, and f), initial state energies, and final state relaxation energies, and it may differ from compound series to compound series. Relations between DFT-calculated orbital energies and ΣχR followed opposite trend directions than binding energy/ΣχR trends. X-ray-induced decomposition of compounds was observed. The results confirmed good communication between molecular fragments. Lower binding energies of both the Ir 4f7/2 and N 1s photoelectron lines are associated with shorter Ir-N bond lengths. Cytotoxic tests showed that 1 (IC50 = 25.1 μM) and 3 (IC50 = 37.8 μM) are less cytotoxic against HeLa cells than cisplatin (IC50 = 1.1 μM), but more cytotoxic than the free β-diketone FcCOCH2COCH3 (IC50 = 66.6 μM).